Exploring the effects of the socio-political dynamics on HRM delivery - Kurdi Nakra, Hussein (Trinity College Dublin. School of Business. Discipline of Business & Administrative Studies, 2023)
Recently, the human resource management (HRM) literature has witnessed a burgeoning interest in examining front-line managers' (FLMs) implementation behaviors of adopted HRM. While this stream of research has made significant progress in identifying and substantiating FLMs' multiple engagement approaches in delivering HRM within an organization, some critical questions as to why FLMs' implementation behaviors vary remain unanswered. By drawing on theories from several disciplines (e.g., social constructionism, power perspective), the contribution of the current dissertation is to expand our knowledge by answering the following research questions: (1) What is the current state of HR devolution literature? (2) What are the unfolding patterns of HRM delivery as influenced by socio-political dynamics involving FLMs, HR professionals, and senior managers? (3) What role and influence do relevant HR actors have on HRM delivery? To do so, a qualitative research design was employed in this dissertation, utilizing a case study approach as the overarching research strategy. The thesis consists of three papers, each with its own research aims and objectives. Collectively, the three papers are logically connected and contribute to answering the overarching research question. The first study (Chapter Four) is a systematic literature review of existing studies on HR devolution, addressing FLMs? involvement in HRM and related topics. Based on 103 reviewed studies published between 1982 and 2020, this study served as an introduction and orientation to the diverse field. It aimed to deepen our understanding of the current state of the HR devolution literature by adopting an evolutionary approach that moved beyond a conventional theme-centric review. The second paper (Chapter Five) empirically explored the interactive processes involving three key actors: HR managers, senior managers, and FLMs by delving into relational power dynamics that develop over an early phase of HR implementation. Using a case study design and grounded theory procedures for data analysis, the results revealed that the enforcing (HR managers) and endorsing actors? (senior managers) authority affect FLMs? enactment of HRM. The findings indicated that although endorsing actors tend to agree with enforcing actors that HRM systems are critical to achieving strategic business outcomes (such as financial performance and employee development), their attitudes towards jointly prioritizing these outcomes differed substantially. The findings of this study showed that the endorsing actors implicitly and sometimes explicitly sanctioned FLMs? adoption of multiple implementation behaviors. Finally, paper three (Chapter Six) conceptualized and discussed the antecedents of HR implementation at an earlier phase. It introduces a new framework combining relational power, role theory, and code-switching perspectives to explore the factors that precede and accompany HR implementation. It addresses the limited understanding of FLMs' psychological experiences amidst diverse intra-group dynamics and competing role expectations. A theoretical framework and relevant propositions are presented. Collectively, the papers contribute to our understanding of why FLMs adopt multiple implementation behaviors. This dissertation focuses on the current debates and challenges associated with HR devolution literature. It builds a theoretical and empirical foundation for the relational dynamics embedded within HR implementation by demonstrating how ongoing interactions and political maneuvers involving HR-related actors can lead to different patterns of HR involvement. By adopting a relational power approach, this thesis extends the traditional view that relies on FLMs' agency in delivering HRM by recognizing that HR implementation research should also include related-HR actors in the discussion.
APPROVED
Keywords: HR devolution; HR implementation; implementation behaviors; front-line managers; socio-political dynamics; evolutionary review.; HR implementation; implementation behaviors; front-line managers; socio-political dynamics; evolutionary review